2016
DOI: 10.15406/jamb.2016.04.00102
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulating and Growth Promoting Activity of Dietary Levamisole on Cirrhinus mrigala Fingerlings

Abstract: The effects of supplementing diets with levamisole on growth, immune response and resistance against pathogenic Aeromonas hydrophila were determined. Fish were assigned to three treatments with different level of levamisole (125, 250 and 500 mg kg¯¹ diet) and the control diet was prepared without levamisole. Cirrhinus mrigala were fed at 4% of their body mass for 60 days. Growth performance, enzyme activities and immunological parameters were analyzed among groups. The total erythrocyte count, total leucocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Other research demonstrated that the isoflavone daidzein has potential as an anti-inflammatory. 26 These results show that EAFB has an immunomodulatory effect, but suggest the need for further examination using higher doses to determine whether at the higher dose EAFB has an anti-inflammatory effect, and it is necessary to determine the concentration of saponins and isoflavone daidzein contained in MEB and EAFB.…”
Section: Discussionmentioning
confidence: 96%
“…Other research demonstrated that the isoflavone daidzein has potential as an anti-inflammatory. 26 These results show that EAFB has an immunomodulatory effect, but suggest the need for further examination using higher doses to determine whether at the higher dose EAFB has an anti-inflammatory effect, and it is necessary to determine the concentration of saponins and isoflavone daidzein contained in MEB and EAFB.…”
Section: Discussionmentioning
confidence: 96%